Adequacy of Flood Relief Shelters: A Case Study in Perak, Malaysia - Zahari, N.Z. (EDP Sciences, 2018)
The recent flood event occurred in 2014 had caused disastrous effects in Peninsular Malaysia in states of Kelantan, Pahang, Terengganu, Perak, Johor and Perlis. Perak state was reported with 12,115 victims from 2,896 families registered at 77 relief shelters. There are several issues encountered by the victims and related agencies which caused inconveniences and interruptions during the flooding period. Besides, the usage of public buildings as relief shelters contributes to deterioration of the infrastructures whereby their suitability, convenient, capacity and safety might not be optimum for longer period of time. This paper focuses on the assessment of relief shelters established in Perak Tengah district, Perak. Standards and guidelines for relief shelters were reviewed according to the most relevant agreed principles for humanitarian response. Data and information in this study were obtained from survey activities, interview sessions and observations. In Perak Tengah, more than 50 of the previous relief shelters were public buildings with low capacity areas. Strategic location of shelters with proper design standards should be established to ensure safe and healthy environment for the victims. Findings from this paper provide important outcomes to serve as better preparation in handling future disaster. Â© The Authors, published by EDP Sciences, 2018.